2017
DOI: 10.1158/0008-5472.can-17-0634
|View full text |Cite
|
Sign up to set email alerts
|

ATM Deficiency Generating Genomic Instability Sensitizes Pancreatic Ductal Adenocarcinoma Cells to Therapy-Induced DNA Damage

Abstract: Pancreatic ductal adenocarcinomas (PDAC) harbor recurrent functional mutations of the master DNA damage response kinase ATM, which has been shown to accelerate tumorigenesis and epithelial-mesenchymal transition. To study how ATM deficiency affects genome integrity in this setting, we evaluated the molecular and functional effects of conditional deletion in a mouse model of PDAC. ATM deficiency was associated with increased mitotic defects, recurrent genomic rearrangements, and deregulated DNA integrity checkp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
100
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 95 publications
(104 citation statements)
references
References 47 publications
3
100
0
1
Order By: Relevance
“…The effects observed with VE-822 were similar to those observed with olaparib, which was employed as a control in these studies [81]. The preclinical efficacy of VE-822 was also assessed in Atm -proficient and -deficient models of Kras -driven PDAC [78]. Specifically, PDAC cells isolated from Ptf1a Cre/wt ;Kras LSL.G12D/wt ;Atm fl/fl mice were significantly more sensitive to VE-822, than Ptf1a Cre/wt ;Kras LSL.G12D/wt ;Atm wt/wt controls in vitro [78].…”
Section: Targeting Defective Dna Repair Pathways In Familial and Spormentioning
confidence: 85%
See 4 more Smart Citations
“…The effects observed with VE-822 were similar to those observed with olaparib, which was employed as a control in these studies [81]. The preclinical efficacy of VE-822 was also assessed in Atm -proficient and -deficient models of Kras -driven PDAC [78]. Specifically, PDAC cells isolated from Ptf1a Cre/wt ;Kras LSL.G12D/wt ;Atm fl/fl mice were significantly more sensitive to VE-822, than Ptf1a Cre/wt ;Kras LSL.G12D/wt ;Atm wt/wt controls in vitro [78].…”
Section: Targeting Defective Dna Repair Pathways In Familial and Spormentioning
confidence: 85%
“…Thus, it has been speculated that it is the HR defect in BRCA1/2 -mutated cancer cells that confers sensitivity to PARP inhibition [73,74]. In line with this concept, further experiments have shown that PARP inhibition is indeed selectively toxic in cancer cells that harbor aberrations in additional HR genes, such as ATM , RAD51 , RAD54 , DSS1 , RPA1 , NBN , ATR , CHEK1 , CHEK2 , FANCD2 , FANCA and FANCC [77,78,79,80,81]. Given that several critical phenotypes that are associated with BRCA1 or BRCA2 deficiency are also detectable in situations where no germline BRCA1/2 mutation can be detected, the term ‘BRCA-ness' has been coined.…”
Section: Targeting Defective Dna Repair Pathways In Familial and Spormentioning
confidence: 99%
See 3 more Smart Citations